ENHANCING QUR'ANIC READING PROFICIENCY: EXPLORING THE EFFECTS OF 'WARSYAH QIRO'AH' ON QUR'ANIC RECITATION SKILLS AT MA'HAD SUNAN AMPEL AL-'ALY UIN MALANG - Nisa’, Rodhiyatun (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The ‘warsyah qiro'ah’ Al-Qur'an program is one of the specialized programs at the religious educational institution focused on Qur'anic studies, acting as a pivotal solution to enhance the Qur'an reading proficiency of students at Ma'had Sunan Ampel Al-‘Aly, Universitas Islam Negeri (UIN) Malang, by providing intensive guidance. This initiative also reflects the institution's (MSAA UIN Malang) concerted attention towards its students' overall Qur'anic reading capability, which necessitates further improvement. Consequently, the essence of the ‘warsyah qiro'ah’ Al-Qur'an is supplementary to other Qur'anic programs. In other words, this workshop is a supportive mechanism for students to augment their skills in reading the Qur'an, in conjunction with their participation in other Qur'anic programs (such as Qur'anic studies and recitation correction, among others). Therefore, this discourse explores the involvement of ‘warsyah qiro'ah’ Al-Qur'an, which inherently operates as a supplement or support in enhancing the Qur'anic reading abilities of students at MSAA UIN Malang, focusing on female students. The implications of the ‘warsyah qiro'ah’ Al-Qur'an for these female students include An enhancement in distinguishing between various Hijaiyyah letters, an improvement in the capacity to apply the rules of Tajwid in recitation, a boost in the fluency of reading the Qur'an (eliminating hesitancy and stuttering), an increase in successful recitation corrections (tashih).